The Existing Analysis of Rice-Fish Integration Farming on Lebak Swamp Land in Terms of Social Economic and Institutional Dimensions - Samsul Alam Fyka; Usman Rianse; Lukman Yunus; Muhammad Aswar Limi (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Rice-fish integration farming is an integrated farming system that combines rice and fish cultivation on the same land, and has developed adaptively in the wetlands of Epeesi Village, South Konawe District. This study aims to identify and analyze the existing social, economic, and institutional conditions in the practice of integrated rice-fish farming as a basis for sustainability assessment. The research employed a combination of descriptive qualitative and quantitative approaches, with primary data collected through structured interviews with 75 rice-fish integration farmers, supplemented by secondary data and field documentation. The results showed that socially, this system is supported by ethnic-based community cohesion, family participation, and local wisdom, which remain sustainable and serve as an adaptive force. From an economic perspective, rice-fish integration can improve household food security and farmers' income through commodity diversification and ecotourism services. However, access to capital and formal markets is still limited. Meanwhile, the institutional aspect reveals that farmers' institutions have been established, but their functions are not yet optimal, with minimal support from extension services and partnerships. These findings confirm that the sustainability of integrated rice-fish farming is highly dependent on the integration of social values, household economic resilience, and the strengthening of local institutions. Therefore, agricultural policies that favor local communities and are based on multi-stakeholder partnerships need to be mainstreamed to encourage the replication of this system as a sustainable agricultural model in marginal ecosystems.